2021
DOI: 10.1101/2021.02.25.432934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chemotherapeutic CX-5461 primarily targets TOP2B and exhibits selective activity in high-risk neuroblastoma

Abstract: Survival in high-risk pediatric neuroblastoma has remained around 50% for the last 20 years, with immunotherapies and targeted therapies having had minimal impact. Here, we identify the small molecule CX-5461 as selectively cytotoxic to high-risk neuroblastoma and synergistic with low picomolar concentrations of topoisomerase I inhibitors improving survival in vivo in orthotopic patient-derived xenograft neuroblastoma mouse models. CX-5461 recently progressed through phase I clinical trial as a first-in-human … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Early reports suggested that the primary anti-tumor activity of CX-5461 arises from inhibition of ribosome biogenesis (Bywater et al , 2012; Drygin et al ., 2011). However, recent studies have revealed that CX-5461 can also induce DNA damage, which seems to act as the primary cause of its cytotoxicity in several cell-lines (Bruno et al , 2020; Negi & Brown, 2015; Pan et al , 2021; Quin et al , 2016; Sanij et al , 2020; Xu et al , 2017). This is proposed to be initiated by the irreversible arrest of RNA polymerase I on rDNA promoter regions, leading to nucleolar stress that propagates into a genome-wide DNA damage response (Mars et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Early reports suggested that the primary anti-tumor activity of CX-5461 arises from inhibition of ribosome biogenesis (Bywater et al , 2012; Drygin et al ., 2011). However, recent studies have revealed that CX-5461 can also induce DNA damage, which seems to act as the primary cause of its cytotoxicity in several cell-lines (Bruno et al , 2020; Negi & Brown, 2015; Pan et al , 2021; Quin et al , 2016; Sanij et al , 2020; Xu et al , 2017). This is proposed to be initiated by the irreversible arrest of RNA polymerase I on rDNA promoter regions, leading to nucleolar stress that propagates into a genome-wide DNA damage response (Mars et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has recently been shown that an accelerated tumor development in Apc min mice lacking the zinc‐finger protein 545, a transcriptional repressor for rRNA synthesis, can be reverted by CX5461 [49]. Besides the mechanism proposed by us, that CX5461 reduces rRNA synthesis, there are additional reports that suggest how CX5461 functions, e.g., by poisoning topoisomerase II or by stabilizing G‐quadruplex DNA structures and, therefore, causing DNA damage [50–52].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of spontaneous development of irreversible loss of clonogenicity/tumorigenicity in HPCs raises the intriguing possibility that HPC phenotypes could be promoted therapeutically to inhibit melanoma progression. Towards this, as our gene expression profiling data indicated activation in LPCs of ribosome biogenesis, we tested pharmacological treatment with CX-5461, an agent in clinical development (55) and with promising activity against a range of cancers (51, 52, 55, 63, 64) that is mediated by inducing DNA damage through TOP2B interactions (65) and inhibiting ribosomal RNA (52). Although CX-5461 induced some cell death, its dominant anti-melanoma effect was induction of senescent HPC phenotypes and transcriptomes.…”
Section: Discussionmentioning
confidence: 99%